2020
DOI: 10.1039/d0cc03905e
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of technetium oxidation states: a new approach

Abstract: A first general strategy for the determination of Tc oxidation state by new approach involving X-ray absorption near edge spectroscopy (XANES) at the Tc L3 edge is shown. A comprehensive...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…The evaluation of Tc K-edge EXAFS data gives relevant insights into structural parameters such as the coordination number and Tc−O distances but does not allow derivation of conclusive chemical models for the Tc(IV)−gluconate complexes prevailing in the aqueous phase. As already hinted in the literature for Tc solid phases, 42,43 our work provides the first evidence on the high sensitivity of L 3 -edge XANES toward the molecular environment of Tc in aqueous samples. The coupling of this highly sensitive technique with ab initio methods represents a prominent tool for the accurate characterization of the molecular environment of Tc in the aqueous phase, thus underpinning the development of accurate chemical and thermodynamic models in real aqueous systems.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The evaluation of Tc K-edge EXAFS data gives relevant insights into structural parameters such as the coordination number and Tc−O distances but does not allow derivation of conclusive chemical models for the Tc(IV)−gluconate complexes prevailing in the aqueous phase. As already hinted in the literature for Tc solid phases, 42,43 our work provides the first evidence on the high sensitivity of L 3 -edge XANES toward the molecular environment of Tc in aqueous samples. The coupling of this highly sensitive technique with ab initio methods represents a prominent tool for the accurate characterization of the molecular environment of Tc in the aqueous phase, thus underpinning the development of accurate chemical and thermodynamic models in real aqueous systems.…”
Section: Discussionsupporting
confidence: 77%
“…As shown below (Section ), attempts for DFT optimizations of the coordination polyhedron of sample B as a basis for ab initio calculations of the corresponding Tc L 3 -edge XANES spectra, as for now, have not been successful. Note that Bauters et al reported a remarkable range of the WL shape and crystal-field splitting for various Tc­(IV) complexes in their recent comprehensive Tc L 3 -edge XANES study of technetium oxidation state signatures depending on the ligand type and the coordination structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the surrounding conditions (such as pH, ionic strength, co-localized complexing agents, and the redox potential of aqueous media), 99 Tc can exist in oxidation states ranging from I to VII in nuclear waste solutions. Various studies have revealed that the environmental mobility of 99 Tc is primarily governed by the tetra- (IV) and heptavalent (VII) oxidation states, while the other oxidation states require stabilizing ligands. In oxic environments, 99 Tc persists as a soluble and highly mobile oxyanion pertechnetate (TcO 4 – , Tc­(VII)), which is also known for eluding targeted waste treatment technologies. Once released into the environment, TcO 4 – does not readily sorb to common near- and subsurface minerals such as ferric (Fe­(III)) minerals or clays, e.g., bentonite, due to its low negative charge. However, if Tc­(VII) is reduced to more stable Tc­(IV) by a natural or synthetic reducing agent, sequestering and immobilizing 99 Tc becomes more favorable.…”
Section: Introductionmentioning
confidence: 99%